A move that's not good for Hadi - New, Straits Times (New Straits Times, 2015)
KUALA LUMPUR: Analysts believe that the nomination of Pas vice-president Datuk Tuan Ibrahim Tuan Man for the party president's post is a clear signal that a challenge will be mounted against party chief Datuk Seri Abdul Hadi Awang in the party polls in June.